Capacity building for pediatric neuro-oncology in Pakistan- a project by my child matters program of Foundation S - Mushtaq, Naureen; Qureshi, Bilal Mazhar; Javed, Gohar; Sheikh, Nabeel Ashfaque; Bakhshi, Saqib Kamran; Laghari, Altaf Ali; Enam, Syed Ather; Anwar, Shayan Sirat Maheen; Hilal, Kiran; Kabir, Arsalan; Ahmad, Alia; Goraya, Amber; et al. (Frontiers in Oncology, 2024)
Initiated in June 2019, this collaborative effort involving 15 public and private sector hospitals in Pakistan aimed to bolster the capacity for pediatric neuro-oncology (PNO) care. Supported by a My Child Matters/Foundation S grant, the initiative achieved significant milestones. It established multidisciplinary tumor boards (MTB) in three different regions of Pakistan, conducting 124 meetings and discussing 545 cases. Over 40 longitudinal lectures were organized to enrich the knowledge, awareness, and expertise of healthcare professionals in PNO care. Two symposia, featuring international collaborators and keynote speakers, sought to raise national awareness of PNO. The initiative led to the development of standardized national treatment protocols for lowgrade glioma, medulloblastoma, and high-grade glioma, with additional protocols currently under development. The launch of Pakistan's first pediatric neuro-oncology fellowship program produced two graduates, increasing the number of trained pediatric neuro-oncologists in the country to three. Efforts are underway to establish a national case registry for PNO. This project exemplifies the potential for capacity building in PNO within low-middle income countries and the success of intranational twinning programs.